Le lointain est ici - Cohen Hadria, Michèle (CV Photo, 2003)
Abstract The Linea de Confine movement in Emilie Romagne (northern Italy), both conceptual and empirical in its relationship with the territory, follows the lineage of Italian photography of the 1970s — with the work of Luigi Ghirri, Franco Vaccari, Ugo Mulas, and others who tried, in their time, to inventory both a highly symptomatic post-industrial landscape, and merchandise, as well as the minimalist materiality of photography. In their wake, the new generation practises a sort of anthropology of the "here" that resonates with a globalization, which it interiorizes on the "local" level, the only yardstick possible of proximity to human beings and to history.